2001
DOI: 10.1097/00129492-200111000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Effects of Hypercholesterolemia on the Cochlea

Abstract: These observations confirm that hypercholesterolemia alone may cause auditory dysfunction if dietary cholesterol is kept at a high level for a long time. Alterations attributed to hypercholesterolemia begin in the stria vascularis and then spread over the outer hair cells, mainly in the basal turn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 13 publications
2
40
0
Order By: Relevance
“…Satar and colleagues noted hearing loss and stria vascularis pathology in guinea pigs fed a highcholesterol diet. 36 Similarly, chinchillas on a high-lipid diet had pathological changes in the stria and outer hair cells. 37 A rabbit study showed that hypertension and high cholesterol had additive effects on hearing although, interestingly, low-frequency hearing improved, whereas high-frequency hearing declined.…”
Section: Discussionmentioning
confidence: 99%
“…Satar and colleagues noted hearing loss and stria vascularis pathology in guinea pigs fed a highcholesterol diet. 36 Similarly, chinchillas on a high-lipid diet had pathological changes in the stria and outer hair cells. 37 A rabbit study showed that hypertension and high cholesterol had additive effects on hearing although, interestingly, low-frequency hearing improved, whereas high-frequency hearing declined.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a well-established risk factor for atherosclerosis and microvascular disorders in the coronary, cerebral and peripheral regions [Marcucci et al, 2005]. A similar role in the impairment of cochlear perfusion, which is a vascular region provided with a terminal capillary bed, is biologically conceivable [Marcucci et al, 2005;Mercier et al, 1999;Satar et al, 2001;Suzuki et al, 2008]. Nevertheless, there are only few reports in the literature concerning the relationship between diabetes mellitus and ISSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…However, impaired angiogenesis may also be involved in the decreased capillary density because hyperlipidemia attenuates angiogenesis in limbs [27,33] . The decreased capillary density may be responsible for lower blood flow in the stria vascularis, and for profound intercellular edema in the marginal layer of the stria vascularis of the hyperlipidemic animal models [5,34] .…”
Section: Discussionmentioning
confidence: 99%